2022
DOI: 10.3389/fimmu.2022.931876
|View full text |Cite
|
Sign up to set email alerts
|

Modulating macrophage function to reinforce host innate resistance against Mycobacterium avium complex infection

Abstract: Mycobacterium avium complex (MAC) is the main causative agent of infectious diseases in humans among nontuberculous mycobacteria (NTM) that are ubiquitous organisms found in environmental media such as soil as well as in domestic and natural waters. MAC is a primary causative agent of NTM-lung disease that threaten immunocompromised or structural lung disease patients. The incidence and the prevalence of M. tuberculosis infection have been reduced, while MAC infections and mortality rates have increased, makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 264 publications
0
3
0
Order By: Relevance
“…The DST results indicated that M. abscessus and M. avium were resistant to almost all the anti-TB drugs used in the DST, and over half of the M. intracellulare and M. avium -intracellulare complex isolates were resistant to anti-TB drugs according to DST results. These findings suggest that there is a high prevalence of drug resistance within NTM strains, particularly to KM, CPM, AMK, and PAS ( Gopalaswamy et al., 2020 ; Park et al., 2022 ). Resistance to other commonly used antibiotics like INH and macrolides such as AZM also appears to be relatively high.…”
Section: Discussionmentioning
confidence: 88%
“…The DST results indicated that M. abscessus and M. avium were resistant to almost all the anti-TB drugs used in the DST, and over half of the M. intracellulare and M. avium -intracellulare complex isolates were resistant to anti-TB drugs according to DST results. These findings suggest that there is a high prevalence of drug resistance within NTM strains, particularly to KM, CPM, AMK, and PAS ( Gopalaswamy et al., 2020 ; Park et al., 2022 ). Resistance to other commonly used antibiotics like INH and macrolides such as AZM also appears to be relatively high.…”
Section: Discussionmentioning
confidence: 88%
“…6 A, deferoxamine significantly rescued M. avium killing within old BMMs to a similar level as seen in young BMMs at 24 and 72 h post-infection. M. avium is an intracellular bacteria pathogen that survives within macrophages by blocking phagolysosome maturation, a process that generally destroys invading bacteria [ 12 , 13 ]. This process can be measured by analyzing the colocalization of fluorescent M. avium and LysoTracker dye.…”
Section: Intracellular Iron Accumulation Increases M Avium ...mentioning
confidence: 99%
“…Upon encountering NTM, macrophages attempt to phagocytose (engulf) the bacteria. However, NTM evolved strategies to manipulate macrophage responses and evade immune detection [ 12 , 13 ]. Some NTM species, such as Mycobacterium avium ( M. avium ), can alter the maturation of the phagosome, hindering lysosomal fusion and thus avoiding exposure to destructive enzymes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%